Film As The Media Of Social Critics About Environment, Structuralism In Film Wall-E - Shochifah Diyah Puspitasari (IQTIDA : Journal of Da'wah and Communication, 2021)
Nowadays, the harmonization between man and nature is always being issues that never stop to be discussed. The human existence and development with the very rapid progress that they have experienced, oftentimes bringing the negative effects to the balance of nature. Then, this fact raises many anxieties that are realized by critics or protests. One of those critics are then visualized trough film which is more acceptable and easier to be understood by society from each social class. Wall-E is one of the movie titles that become a representation of that opinion. Using qualitative research with the structuralism approach, the author tries to find out about how the critics and messages delivered constructively to the world society. The result of this research can be concluded that Wall-E, a film that produced by Disney cooperate with Pixar and directed by Andrew Stanton, constructively tries to deliver the critics and messages to educate the society from all ages. Hopefully, peoples can be wiser in carrying out life in the world with the spirit of conservation.